2012
DOI: 10.1080/00221686.2012.729540
|View full text |Cite
|
Sign up to set email alerts
|

Coherent structures in flow over hydraulic engineering surfaces

Abstract: Wall-bounded turbulence manifests itself in a broad range of applications, not least in hydraulic systems. Here, we briefly review the significant advances over the past few decades in the fundamental study of wall turbulence over smooth and rough surfaces, with an emphasis on coherent structures and their role at high Reynolds numbers. We attempt to relate these findings to parallel efforts in the hydraulic engineering community and discuss the implications of coherent structures in important hydraulic phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 97 publications
7
92
0
3
Order By: Relevance
“…Nezu 2005) that indicate the presence of long rotational motions resembling VLSMs in pipes, closed channels and boundary layers. A fairly comprehensive review of long rotational motions that are occasionally reported for OCFs can be found in Adrian & Marusic (2012). They stated that the 'close relationship between meandering VLSMs of turbulence structure research and the long cellular motions of open-channel flow research is impossible to ignore.…”
mentioning
confidence: 99%
“…Nezu 2005) that indicate the presence of long rotational motions resembling VLSMs in pipes, closed channels and boundary layers. A fairly comprehensive review of long rotational motions that are occasionally reported for OCFs can be found in Adrian & Marusic (2012). They stated that the 'close relationship between meandering VLSMs of turbulence structure research and the long cellular motions of open-channel flow research is impossible to ignore.…”
mentioning
confidence: 99%
“…In this method, the Reynolds stresses were partitioned into four events: ejection, sweep, inward interaction, and outward interaction events (Adrian and Marusic 2012;Nezu 2005) (Fig. 4).…”
Section: Secondary Currentsmentioning
confidence: 99%
“…In the last few years, a number of papers have reviewed developments in hydraulics and ecohydraulics, as well as the prospect for future research directions [Nezu, 2005;Adrian and Marusic, 2012;Nepf, 2012]. In addition, experimental and eddy-resolving numerical work has highlighted the important role played by coherent flow structures in a variety of fluvial processes [Adrian and Marusic, 2012;Venditti et al, 2013] and more work could be done to link these to the recent developments in our understanding of boundary layer fluid mechanics [Ganapathisubramani et al, 2005;Marusic et al, 2010;Guala et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, a number of papers have reviewed developments in hydraulics and ecohydraulics, as well as the prospect for future research directions [Nezu, 2005;Adrian and Marusic, 2012;Nepf, 2012]. In addition, experimental and eddy-resolving numerical work has highlighted the important role played by coherent flow structures in a variety of fluvial processes [Adrian and Marusic, 2012;Venditti et al, 2013] and more work could be done to link these to the recent developments in our understanding of boundary layer fluid mechanics [Ganapathisubramani et al, 2005;Marusic et al, 2010;Guala et al, 2011]. Reviews of the potential for eddy-resolving numerical methods in the fluvial sciences have also appeared [Keylock et al, 2012a;Constantinescu, 2014;Stoesser, 2014], highlighting the techniques available and the advances in knowledge necessary in order to formulate methods tailored to hydraulics and geomorphological applications [King et al, 2012;Schmeeckle, 2014].…”
Section: Introductionmentioning
confidence: 99%